Integrating a multinational company through values management - Hirvonen, Anne (My University, 2006)
The purpose of this study was to find out, what kind of impacts the global integration of the values has on the personnel. The study researched the change of values and behaviour in different units of the case company Outokumpu Technology. The integrator tool that was studied was OT’s values management program called Journey of Values. There is not much previous research in this particular topic. Hence, it is a current topic to study, due to the globalisation of businesses and their need for integration, and also due to, a great impact of the values in the company. Theoretical part focused on two main frameworks: values in organisation and global integration of values. The importance of values in an organisation is agreed to be significant by scholars. Values are the core of a company’s strategy and culture. HRM plays a key role in a global integration process of culture and values. Therefore it is examined in the study carefully. The study has both the quantitative and the qualitative data, which was collected by the survey questionnaire and by the group interview. The results of this study showed that the values of the personnel have changed after the Journey of Values. The importance of management’s role in the integration was emphasised, and also how every implemented procedure (Journey of Values) should be reinforce regularly. According to this study co-operation and teamwork, openness and communication were the values, which changed the most.
Keywords: values; culture; integration and IHRM; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|